Implementation of a comprehensive hospitalist‐led initiative to improve care for patients with opioid use disorder. Issue 6 (10th May 2022) - Clifton, Dana; Ivey, Noel; Poley, Stephanie; O'Regan, Amy; Raman, Sudha R.; Frascino, Nicole; Hamilton, Shavone; Setji, Noppon
Abstract: Background: As opioid‐related hospitalizations rise, hospitals must be prepared to evaluate and treat patients with opioid use disorder (OUD). We implemented a hospitalist‐led program, Project Caring for patients with Opioid Misuse through Evidence‐based Treatment (COMET) to address gaps in care for hospitalized patients with OUD. Objective: Implement evidence‐based treatment for inpatients with OUD and refer to postdischarge care. Design, Setting, and Participants: Project COMET launched in July 2019 at Duke University Hospital (DUH), an academic medical center in Durham, NC. Intervention, Main Outcomes, and Measures: We engaged key stakeholders, performed a needs assessment, and secured health system funding. We developed protocols to standardize OUD treatment and employed a social worker to facilitate postdischarge care. Electronic health records were utilized for data analysis. Results: COMET evaluated 512 patients for OUD during their index hospitalization from July 1, 2019 through June 30, 2021. Seventy‐one percent of patients received medication for OUD (MOUD) during admission. Of those who received buprenorphine during admission, 64% received a discharge prescription. Of those who received methadone during admission, 83% of eligible patients were connected to a methadone clinic. Among all patients at DUH with OUD, MOUD use during hospitalization and at discharge increased in the post‐COMET period compared to the pre‐COMET period ( p  < .001 for both). Conclusion: Our program is one of the first to demonstrate successful implementation of a hospitalist‐led, comprehensive approach to caring for hospitalized patients with OUD and can serve as an example to other institutions seeking to implement life‐saving, evidence‐based treatment in this population.